The Current Non-Status of General Equilibrium Theory - Donald W. Katzner (University of Massachusetts, Department of Economics, 2004)
This paper argues that the abandonment of general equilibrium theory by microeconomists was a mistake. It provides counter arguments to two of the reasons for that abandonment - lack of both generality and consistency with methodological individualism in uniqueness and stability analysis of equilibria - and urges microeconomists to refocus some of their attention on it.
Keywords: D50; 330; general equilibrium theory; price determination; methodological individualism